Tanggung Jawab Direksi Terkait Rapat Umum Pemegang Saham (RUPS) Tahunan - Noija, Gloria Gracia; Pesulima, Theresia Louize; Pariela, Marselo Valentino Giovani (KANJOLI Business Law Review, 2025)
The Annual General Meeting of Shareholders is an important forum for shareholders to obtain the Board's accountability report on the management of the company over the past financial year. The Board, as the company's organ responsible for its operations, has the obligation to hold the Annual General Meeting in accordance with applicable laws and regulations. Based on Law Number 40 of 2007 concerning Limited Liability Companies Article 78 Paragraph 2 of the Company Law, the annual General Meeting of Shareholders (RUPS) must be held no later than six months after the end of the financial year. However, the reality is that there are still companies that do not hold the RUPS. The type of research used is a normative legal approach with a Statutory Approach and a Conceptual Approach. The legal materials used are primary and secondary legal materials which are analyzed qualitatively to answer the problems being studied. The Board of Directors is fully responsible for the implementation of the Annual General Meeting of Shareholders, which includes the obligation to hold the meeting no later than six months after the end of the financial year, to prepare and submit an annual report to the shareholders, and to ensure that the financial statements have been audited by a public accountant if required. The Board of Directors is also required to be present at the General Meeting to provide explanations regarding the company's performance and condition, as well as to follow up on any decisions made during the meeting. The entire implementation process of the GMS must be carried out in accordance with the provisions of the Company Law, the company's articles of association, and the principles of good corporate governance. Meanwhile, the Board of Directors that does not hold the GMS obviously contradicts the provisions of the Company Law, particularly Article 78 Paragraph (2), and can be categorized as an unlawful act if it fulfills the elements in Article 1365 of the Civil Code.